2010
DOI: 10.3109/03009741003781985
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and subclinical atherosclerosis in systemic sclerosis: consequences of previous corticosteroid treatment

Abstract: Our study confirms an increased prevalence of subclinical atherosclerosis in SSc patients and demonstrates a hitherto unknown association with corticosteroid cumulative dosage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 13 publications
3
18
3
1
Order By: Relevance
“…In contrast to the previous findings, other studies [25][26][27][28][29][30][31] found that the mean common carotid arteries IMT were not significantly increased compared with healthy controls. The differences between the results of the present study and the results of these studies may be due to the larger percentage of diffuse cutaneous SSc subtype in these studies compared with ours.…”
Section: Discussioncontrasting
confidence: 89%
“…In contrast to the previous findings, other studies [25][26][27][28][29][30][31] found that the mean common carotid arteries IMT were not significantly increased compared with healthy controls. The differences between the results of the present study and the results of these studies may be due to the larger percentage of diffuse cutaneous SSc subtype in these studies compared with ours.…”
Section: Discussioncontrasting
confidence: 89%
“…Our patients were younger than the patients in other published series where it has been shown that the disease mostly affects women in their 4th or 5th decade of life [4][5][17][18][19]. Limited cutaneous involvement was predominant, which was expected [4][5]20]. Though the mean duration of Raynaud's was more in dcSSc than lcSSc, this difference was not statistically significant (Table 5).…”
Section: Discussioncontrasting
confidence: 60%
“…Subclinical atherosclerosis has been reported in both SLE as well as RA in various studies [3]. There is increasing evidence that atherosclerosis occurs prematurely in systemic sclerosis [4][5][6]. Although micro vascular disease is characteristic of SSc, but there is growing evidence of macro vascular disease in SSc patients.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning disease characteristics, disease duration, anticentromere antibody positivity, cumulative glucocorticoid dose, and MRSS (negatively) have been reported to be associated with CVD and/or atherosclerosis in SSc (36,37,41,43). However, PAH was found to be associated with CVD only in a systematic review of the prevalence of coronary heart disease in SSc (1).…”
Section: Discussionmentioning
confidence: 99%
“…However, so far, only 1 study evaluated the consequences of previous glucocorticoid use on atherosclerosis in SSc patients (37). That study reported that higher cumulative glucocorticoid intake was associated with higher cIMT (OR 1.15).…”
Section: Discussionmentioning
confidence: 99%